PENERAPAN METODE MIND MAPPING DALAM CERITA LEGENDA âBATU KARANG IGOMUâ SUKU MEYAH SEBAGAI ALTERNATIF PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN - Iwanggin, Musa Alex (Universitas Papua Manokwari, 2016)
This paper aims to reveal the application of mind mapping method proposed by Buzan (2008) in which mind mapping can help students in many ways such as: to plan, to communicate, to be creative, to solve problem, to focus, to organize and to finish thought, to remember well, to learn more quickly and efficiently and to train the whole picture of the story.The fact illustrates that the level of reading ability has declined. The decline is also balanced by a decreasing in the level of studentsâ understanding on reading text which is being read. To that end, the selection of the legend of Papua folklore âRock Igomuâ coming from Meyah in Manokwari, as a learning medium to improve the ability of reading comprehension can be based on the primary assumption that the context of everyday lives of students or learners Â has been familiar and fused with the legend. In addition, the selection of this legend can increase studentsâ or learnersâ treasure of knowledge or cognition as Papuanchildren who are the next generation and the heir of the story.Â